The effect of the Iraqi dinar exchange rate on inflation and economic growth using the joint integration methodology "a standard study" - huseen, Ghufran noori; moslem, Hamdia shaker (Journal of Economics and Administrative Sciences, 2020)
The exchange rate is of great importance at the global and local levels alike, as this importance increases with the increasing rates of development of economic relations between countries of the world due to openness and integration into the global economy, expressed by the expansion of the volume of trade and financial relations between countries. The Central Bank of Iraq has set the need to stabilize this price as a goal to reduce inflation rates and reduce them to the internationally accepted rates by using the foreign currency sale window to achieve a balance between the forces of supply and demand for foreign currency and to preserve the value of the Iraqi dinar. The research concluded that the central bank was It has a major role in influencing inflation rates in the economy after the CPA issued Law No. (56) of 2006 and this came as a result of the success of the CBI policy in targeting inflation as a primary objective of the monetary policy, through the currency sale window, which was able to improve the exchange rate of the dinar. Against the dollar, to achieve relative stability in the official and parallel markets, which reflected positively on the inflation rate and it’s reaching very low levels. There is also a disconnect in the relationship between changes in the exchange rate and the real product without oil, while the research recommended the necessity of work by the monetary authority represented by CPI that the exchange rate of the dinar is high in light of the scarcity of non-oil exports, weak domestic production and reliance on bridging the demand gap on the importer from abroad. Going to reduce that price, as well as the necessity to continue to follow the current exchange rate regime (the fixed exchange system) .